2013
DOI: 10.1097/spv.0b013e31829099c1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2011 FDA Transvaginal Mesh Safety Update on AUGS Members’ Use of Synthetic Mesh and Biologic Grafts in Pelvic Reconstructive Surgery

Abstract: Synthetic mesh use in transvaginal POP surgery decreased after the 2011 FDA safety update, but synthetic mesh use for transabdominal POP repair and sling procedures and overall biologic graft use in POP surgery did not decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 5 publications
1
41
0
Order By: Relevance
“…Survey questions were developed based on the type of questions sent to members of the American Urogynecology Society to assess the impact of the 2011 FDA transvaginal mesh safety update regarding the use of synthetic mesh for pelvic reconstructive surgery [18]. The survey was pilot tested by experts in minimally invasive gynecology before final implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Survey questions were developed based on the type of questions sent to members of the American Urogynecology Society to assess the impact of the 2011 FDA transvaginal mesh safety update regarding the use of synthetic mesh for pelvic reconstructive surgery [18]. The survey was pilot tested by experts in minimally invasive gynecology before final implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a big debate started concerning the standardization of surgical techniques for treatment of pelvic floor dysfunc-www. journals.viamedica.pl/ginekologia_polska tions, especially those due to Food and Drug Administration (FDA) statements regarding the use of artificial prostheses in urogynaecology [4]. Surgeons should also remember that advanced age itself, regardless of accompanying comorbidities, will increase the risk of postoperative complications when compared to younger counterparts undergoing the same surgical procedures [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey at the November 2011 meeting of the American Association of Gynecologic Laparoscopists (AAGL), 72 % reported that they performed surgery for prolapse and/or incontinence, and 53.7 % reported changing their methods of counseling after the FDA 2011 warning [15]. The American Urogynecologic Association (AUGS) sent an electronic survey to its members between January 2011 and December 2012 and found that 40 % of its members who answered the survey reported decreased use of transvaginal mesh for prolapse while 12 % stopped its use altogether [16].…”
Section: Prevalence Of Use After 2011mentioning
confidence: 96%